Pragmatics and The Philosophy of Language Acts Found in The Girl Who Fell Beneath The Sea Novel by Axie Oh - Istihayyu Buansari; Zuriyati Zuriyati; Saifurrohman Saifurrohman (Pujangga: Jurnal Bahasa dan Sastra, 2022)
This study aims to identify the types of directive illocutionary acts by Searle and perlocutionary acts by Austin, which occur in the novel The Girl Who Fell Beneath the Sea by Axie Oh. The researcher used descriptive-qualitative method. The data of this study were taken from 282 utterances containing directive illocutionary acts. The first result shows that only seven of the eleven types of directive illocutionary acts were found; ask (175), beg (11), command (8), demand (29), command (36), ask (8), and warn (15). The results of these two studies showed two types of perlocutionary acts, namely successful (175) and unsuccessful (107).